Una esperienza di psicodramma analitico al SerDP San Giovanni in Persiceto. Un progetto di miglioramento (2019-2023) - Di Caro, Silvia; Favaro, Giulia (Mission - Open Access, 2024)
The device of analytic psychodrama with its own peculiar characteristics, according to the method developed by Dr. Lemoine, at the design level, was well suited to the medium to long-term treatment needs of patients in charge of SerDP. The experience itself was innovative with respect to the field of application, it met the design expectations not only from a clinical point of view, but also from an economic point of view. The most important part, however, remains the clinical one, and from this point of view the numbers represented in the tables of the text are also encouraging. An important fact to underline concern the effectiveness of the method in its progress, which not only confirmed the expected expectations, but also exceeded them. From this we can deduce the reproducibility of the experience, which has as an indispensable condition a thorough training of the two psychotherapists involved in its application.